Efficacy and Safety of Colchicine in Post–acute Myocardial Infarction Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Diaz-Arocutipa, Carlos; Benites-Meza, Jerry K.; Chambergo-Michilot, Diego; Barboza, Joshuan J.; Pasupuleti, Vinay; Bueno, Héctor; Sambola, Antonia; Hernandez, Adrian V. (Frontiers in Cardiovascular Medicine, 2021)
Background: Inflammation plays a key role in atherosclerotic plaque destabilization and adverse cardiac remodeling. Recent evidence has shown a promising role of colchicine in patients with coronary artery disease. We evaluated the efficacy and safety of colchicine in post–acute myocardial infarction (MI) patients. Methods: We searched five electronic databases from inception to January 18, 2021, for randomized controlled trials (RCTs) evaluating colchicine in post–acute MI patients. Primary outcomes were cardiovascular mortality and recurrent MI. Secondary outcomes were all-cause mortality, stroke, urgent coronary revascularization, levels of follow-up high-sensitivity C-reactive protein (hs-CRP), and drug-related adverse events. All meta-analyses used inverse-variance random-effects models. Results: Six RCTs involving 6,005 patients were included. Colchicine did not significantly reduce cardiovascular mortality [risk ratio (RR), 0.91; 95% confidence interval (95% CI), 0.52–1.61; p = 0.64], recurrent MI (RR, 0.87; 95% CI, 0.62–1.22; p = 0.28), all-cause mortality (RR, 1.06; 95% CI, 0.61–1.85; p = 0.78), stroke (RR, 0.28; 95% CI, 0.07–1.09; p = 0.05), urgent coronary revascularization (RR, 0.46; 95% CI, 0.02–8.89; p = 0.19), or decreased levels of follow-up hs-CRP (mean difference, −1.95 mg/L; 95% CI, −12.88 to 8.98; p = 0.61) compared to the control group. There was no increase in any adverse events (RR, 0.97; 95% CI, 0.89–1.07; p = 0.34) or gastrointestinal adverse events (RR, 2.49; 95% CI, 0.48–12.99; p = 0.20). Subgroup analyses by colchicine dose (0.5 vs. 1 mg/day), time of follow-up (<1 vs. ≥1 year), and treatment duration (≤30 vs. >30 days) showed no changes in the overall findings. Conclusion: In post–acute MI patients, colchicine does not reduce cardiovascular or all-cause mortality, recurrent MI, or other cardiovascular outcomes. Also, colchicine did not increase drug-related adverse events.